Establishment the Synchronization System for Mass Clonal Propagation of Sugarcane (Saccharumofficinarum L) through Shoot tip Culture - Khaskheli, Mazhar Ali; Baloch, Shahla Karim; Ali, Muhram; Nizamani, Ghulam Shah; Yasmeen, Shafqat; Khaskheli, Allah Jurio; Khaskheli, Sajad Ali; Rahman, Anees-ur–; Qambrani, Rawal Ahmed; Qazi, Amna (International Journal of Environment, Agriculture and Biotechnology, 2019)
The aim of present investigation was to examine the efficiency of three different sugarcane (Saccharumofficinarum L.) verities viz. NIA 1026-P7, NIA-87 and SG NIA-2476.A total of 20 explants (apical meristems) shoot tip were inoculated on MS Basal media along with various concentrations of 2, 4-D, BAP, Kinetin and IAA. The results of different verities showed that initial growth, number of micro shoots and shoot length was obtained in variety NIA-1026-P7, on MS medium supplemented with low concentration of 2, 4Dichlorophenoxyacetic acid (2, 4-D) along with highest concentration of Benzyl aminopurine (BAP) and Kinetin. The variety SG NIA 2476 expressed modestly and was not sufficient as compared with other varieties. The established plantlets were transferred on the MS half strength rooting medium along with various concentrations of IBA and IAA. The results of different varieties showed that maximum number of micro roots and roots length were established in variety NIA 87, on the half strength MS medium plus 1.50 mg/l IBA, 3.0 mg/l IAA and 25 g/l of sugar.